Children Surviving Post-Univentricular Repair: Single Center Experience - Lamia Abdelrahman Ibrahim; Fatma Al Zahraa Mostafa; Baher Matta Hanna; Noha Ali Abd El Salam (Pediatric Sciences Journal, 2023)
Background: The children population who underwent single ventricle repair is growing in number with longer follow up periods and increased frequency of complications. Aim of work: To evaluate the outcome and complications post Glenn and Fontan single ventricle repair in children. Material and Methods: A retrospective study of data within files of all surviving patients post univentricular surgical repair, who were following up at Post Cardiac Interventions Clinic in Cairo University Children Hospital from October 2007 until October 2020. Results: The files of 113 patients were enrolled in the study, 93 (82.3%) of them were post Glenn operation. Their mean± SD age at the time of the operation was 1.4± 0.9years, and mean follow up duration of 8.3 ±3 years. The study included 20 (17.7%) patients post Fontan operation, with a mean age at the time of the operation of 7.82± 1.63years, and mean follow up duration of 4.75 ±0.08 years. They were 77 (68.15%) males, and 36(31.85%) females. Complications post Glenn operation were heart failure in 34(36.5%) patients, pericardial and pleural effusion in 4 (4.3%) and hypoalbuminemia in 2 (2.15%). Complications post Fontan were heart failure in 4 (20%) patients, arrhythmia in 2 (10%), and protein losing enteropathy in 2 (10%). Frequency of complications was not related to the age at the time of the Glenn and Fontan operation (p =0.793) and (p=0.079) respectively. Conclusion: Performing Glenn and Fontan at older age was not related to the frequency of complications in our patients. Heart failure was the most common complication post Glenn and Fontan operations.